2019
DOI: 10.1111/asj.13223
|View full text |Cite
|
Sign up to set email alerts
|

Admixture analyses and phylogeographic relationships reveal complete genetic distinctiveness of Polish farm and wild red foxes (Vulpes vulpes) and the North American origin of farm‐bred individuals

Abstract: A number of studies showed that many mtDNA haplotypes were shared among contemporary farm red foxes bred on different continents and the historical wild red foxes of North American origin. Therefore, in this study, the population genetic structure and phylogeographic relationships of Polish red foxes kept on fur farms and their wild conspecifics were investigated to assess the ancestry of the farm red foxes in Poland. A total of 330 tissue samples (200 from farm foxes and 130 from wild foxes) were used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…The lack of significant “import” effects indicates a relatively high degree of similarity of the world population of red foxes. This finding is in line with the results of the phylogenetic and phylogeographic studies conducted by Zatoń‐Dobrowolska et al (2019). They showed the North American origin of the Polish red fox population kept on fur farms.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of significant “import” effects indicates a relatively high degree of similarity of the world population of red foxes. This finding is in line with the results of the phylogenetic and phylogeographic studies conducted by Zatoń‐Dobrowolska et al (2019). They showed the North American origin of the Polish red fox population kept on fur farms.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous research [ 41 ], we identified 23 concatenated haplotypes in wild foxes and 8 concatenated haplotypes in farm foxes (which were reused in the present study). In this study, of the 23 concatenated haplotypes previously reported, we detected 20 (the missing haplotypes were: 3-P02, FOX22-FOX44 and KHARKIV10-RS56).…”
Section: Discussionmentioning
confidence: 99%
“…The PCR mixtures were prepared using a DreamTaq Master Mix kit (Thermo Scientific, Waltham, MA, USA) according to the manufacturer’s protocol. A new set of primers for both sequences, designed by the authors of this study, as well as the thermal cycle conditions for both markers were described by Zatoń-Dobrowolska et al [ 41 ]. The mtDNA sequences (the newly detected ones were submitted to GeneBank) used in this study were previously tested by Zatoń-Dobrowolska et al [ 41 ].…”
Section: Methodsmentioning
confidence: 99%